PENETAPAN PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK ETANOL 70% DAUN JAMBU AIR (Syzygium samarangense) DARI KECAMATAN GUBUG - Sari, Gigih Kenanga (Universitas Pahlawan Tuanku Tambusai, 2024)
A local plant that contains a lot of antioxidants is the water guava (Syzygium samarangense). Water guava leaves are extracted using the maceration method. The extract obtained was 156.33 gr. The extract obtained then in the specific water guava extract parameters showed that in the organoleptic test it was dark green to brownish, had a thick aroma typical of the leaves, thick liquid form, was positive for ethanol free, phytochemical screening and TLC showed flavonoids, saponins, tannins and triterpenoids. The non-specific parameters of water guava extract showed water content of 8.5%, drying loss of 9.08%, ash content of 11.12%, specific gravity of 0.931, and all non-specific parameters met the standards.